THE EFFECT OF GINGER BISCUIT ON NAUSEA AND VOMITING IN EARLY PREGNANCY - Z Basirat (Babol University of Medical Sciences, 2006)
BACKGROUND & OBJECTIVE: Nausea and vomiting of early pregnancy (NVP) are often alleviated by eating dried biscuits or food. Natural products such as ginger have been suggested as herbal medicine for its treatment. The purpose of this study was to determine the effectiveness of ginger in biscuit form for the treatment.METHODS: This study was performed on 65 pregnant women with NVP before 17 weeks’ gestation during 2004-2005. The subjects were randomized in a double-blind design and divided into two groups to take biscuits. Ginger (0.5 g) as fine powder was incorporated in each biscuit. Subjects received 5 ginger biscuits per day or an identical placebo biscuit for 4 days. They graded their severity of nausea using visual analog scales and recorded the number of vomiting episodes in the previous 24 hours and again during 4 consecutive days. Obtained data between two groups were compared using Mann-Whitney, Wilcoxon Sumrank and Kruskall-Wallis H tests.FINDINGS: All subjects except 3 in the ginger group remained in the study. The visual analog scores of post-therapy minus baseline nausea decreased significantly in ginger (2.6±1.83) compared with the placebo group (1.4±1.97, p=0.015). The number of vomiting episodes also decreased in ginger (0.96±1.2) and placebo group (0.6±1.4). CONCLUSION: Ginger in biscuit form is effective for relieving the severity of nausea and vomiting of pregnancy.